Pelatihan Penelitian Tindakan Kelas (PTK) untuk Guru SMP Negeri 2 Wedarijaksa, Pati - gunawan setiadi (Universitas Muria Kudus, 2023)
This proposal community service program is designed to provide and assist the teachers to understand a classroom action research. The basic for proposing this service is the existence the problems, the teacher ability to understand a classroom action research, unable to make a research proposal and unable to make a research report. The activities that will be carried out in this service are to provide a in-house training. The objectives to be achieved are: 1) increasing the understanding of a classroom action research, 2) increasing ability to write a research proposal, and 3) increasing ability to write a research report. The approach offered in the realization of this service is a in house-training model. Keywords: a classroom action research, a research proposal, research report.